Exposição a fatores de risco e prevalência de HIV/ AIDS e sífilis entre gestantes adolescentes e adultas jovens atendidas em programas de referência para DST/HIV/AIDS - Santos, Brena Carneiro (2010)
Adolescent pregnancy has been prominent on the agendas of the Health System in discussions with national and international bodies, considering the psychosocial and clinical implications for pregnant women and newborns, being seen now as a public health problem. When associated with pregnancy, exposure to STD acquires greater dimension. Miscarriages, stillbirths, low birth weight, congenital and perinatal infections are related to untreated STDs in women, in addition to increased risk of infection with human immunodeficiency virus (HIV). HIV and syphilis are diseases that have greater damage to maternal and child health, and therefore require more attention, especially in the prenatal period. Objective: study the prevalence and exposure to HIV/SIDA and Syphilis among pregnant adolescents and young women referred by the Public Health System/SUS for serological screening in Feira de Santana’s STD/SIDA Program (2004-2008). Method: descriptive study with 3030 pregnant. We studied serology, exposure factors and risks, with casual and fixed partners according to age of the pregnant. We evaluated the association of exposure, according to partner type and age of pregnant, through the prevalence ratio/PR. Results: pregnant teenagers and young women showed greater proportions of stable partnership. The unusual use of condoms appear as main exposure and the reasons for this behavior have been related to partner, personal or environmental factors. The group ≤ 16 years differed from the young women, with a lower frequency of condom use, motivated by personal factors, while young women are motivated by factors associated to the partner, with significant results. The prevalences of diseases agreed with the literature. Conclusions: younger adolescents used condoms less because of personal and environmental factors, while young women attach this to their partners, suggesting behavioral and gender issues interfering in the vulnerability, showing the importance of preventive actions.